Laparoscopic management of renal and hepatic hydatidosis in a child: a case report and review of literature - Patil, Rajashekhar T.; Parelkar, Sandesh V.; Sanghvi, Beejal (International Surgery Journal, 2017)
Hydatidosis is an endemic disease caused by Echinococcus granulosus. Humans are accidental intermediate hosts. In children, it affects the lung in 64% of cases and the liver in 28%. Renal involvement is uncommon (2-4%). We operated 7 years old girl with renal and hepatic hydatidosis laparoscopically. Hydatid cyst should be kept as one of differential diagnosis while managing cystic disease of any organ in the body. To the best of our knowledge this is the first case of renal hydatidosis with hepatic hydatidosis that has been managed laparoscopically. Laparoscopic surgery is safe and efficacious in managing multiorgan hydatid disease in children.